Hermann von Helmholtz and the aesthetics of the acoustics. (1st January 2021) - Mion, Marta; Martini, Alessandro
Abstract: Objective: The aim of this study was to honour the 100-year birth jubilee of Hermann von Helmholtz (1821–1894), and his studies on the 'aesthetics of acoustic'. Methods: We will present original documents and historical references. Results: After a brief section of biographical notes on von Helmholtz, we present the results of his acoustic studies and the analysis of his work 'On the sensation of tone'. Conclusion: von Helmholtz devoted part of his researches to acoustics, also creating new tools of his invention as his eponymy named resonators.